PPENGARUH INTERVENSI ORAL MOTOR (PIOMI) TERHADAP KEMAMPUAN REFLEK HISAP BAYI PREMATUR: Effectiveness of Oral Motor (PIOMI) on a Premature Infant Sucking Reflex (Jurnal Kesehatan Siliwangi, 2022)
Premature infant or babies who born at gestation age less than 37 weeks have a speciality in nourishing, which is it has to do with the maturity of the development of oral motor function in infants. Although sucking reflex components are already there at 28 weeks of gestation age, but the synchronization is still irregular. Meanwhile, sucking reflex is an important ability for babies to get adequate nutrition, thus preventing the baby from becoming undernourished, caused by lateness of breast feeding-ability, low weight, and dehydration. This evidence based case report is intended to identify the impact that PIOMI on the ability to sucking reflex of premature babies. Some article on the impact of PIOMI on the ability to sucking reflex of premature infant are carried out in PubMed, Cochrane Library and Google Scholar. Its obtained three articles with randomized controlled trials and meets predetermined criteria of inclusions, then do the journal study, and it is obtained if PIOMI affects the ability to sucking reflex to preterm infants and can be applied to patients. Key words: Oral Motor, Intervention, PIOMI, Preterm, Premature.